2020
DOI: 10.1101/2020.05.24.112722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NK cells and CTLs are required to clear solid tumor in a novel model of patient-derived-xenograft

Abstract: Existing patient-derived-xenograft (PDX) mouse models of solid tumors lack a fully tumor-donor matched "syngeneic" and functional immune system. We developed such a model by engrafting lymphopenic recipient mice with a fresh undisrupted piece of solid tumor, whereby tumorinfiltrating lymphocytes (TIL) expanded in the recipient mice for several weeks. Tumors engrafted in about seventy to eighty percent of syngeneic-immune-system-PDX (SIS-PDX) mice, which harbored tumor-exhausted immune-effector and functional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 67 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…The addition of IL-15 to PD-1 blockade completely abrogated tumor escape from ICI, resulting in a powerful additive therapeutic effect capable of tumor eradication. These findings support a key role for adjuvant IL-15 treatment to induce an immune cell-mediated tumor attack, which can prevent tumor escape from checkpoint blockade therapy, as shown using our novel LUAD-SIS-PDX model (418).…”
Section: Pre-activated Nk Cell Products For Cancer Immunotherapysupporting
confidence: 80%
See 2 more Smart Citations
“…The addition of IL-15 to PD-1 blockade completely abrogated tumor escape from ICI, resulting in a powerful additive therapeutic effect capable of tumor eradication. These findings support a key role for adjuvant IL-15 treatment to induce an immune cell-mediated tumor attack, which can prevent tumor escape from checkpoint blockade therapy, as shown using our novel LUAD-SIS-PDX model (418).…”
Section: Pre-activated Nk Cell Products For Cancer Immunotherapysupporting
confidence: 80%
“…One of our preclinical studies found that the combination of PD-1 blockade and IL-15 signaling resulted in eradication of transplanted lung adenocarcinoma (LUAD) cells in about one-half of treated LUAD-SIS-PDX mice, while the other half presented with a partial response. Notably, IL-15 alone, without PD-1 blockade, significantly reduced tumor burden in all treated LUAD-SIS-PDX animals ( 418 ). PD-1 blockade alone transiently prevented tumor growth, but tumors grew at a similar rate to untreated control tumors after 2 weeks.…”
Section: Pre-activated Nk Cell Products For Cancer Immunotherapymentioning
confidence: 98%
See 1 more Smart Citation
“…Expression of HLA class I was increased in melanoma cells when insufficient numbers of NK cells were present to eradicate all melanoma cells (Balsamo et al, 2012;Huergo-Zapico et al, 2018). Kohlhapp et al (2015) and Xu et al (2004) the eradication of melanoma, and Le et al (2020) found that both CTL and NK cells are important for control of solid tumours in a novel patient-derived xenograft model. Neubert et al (2016) developed a well-controlled co-culture assay for human melanoma and CTL to analyse future T cell-based immunotherapies.…”
Section: Discussionmentioning
confidence: 91%
“…HLA class I expression was increased in melanoma cells in case insufficient NK cell numbers were present to eradicate all melanoma cells (Balsamo et al , 2012; Huergo-Zapico et al , 2018). Kohlhapp et al and Xu et al analysed the roles of murine CTL and NK cells with the result that both cytotoxic cell types are involved in the eradication of melanoma (Xu et al , 2004; Kohlhapp et al , 2015), and in addition Le et al found that both CTL and NK cells are important to control solid tumours in a novel patient-derived xenograft model (Le et al , 2020). Neubert et al developed a well-controlled co-culture assay for human melanoma and CTL to analyse future T-cell based immunotherapies (Neubert et al , 2016).…”
Section: Discussionmentioning
confidence: 99%